Pentingnya Sosialisasi Pemahaman Pancasila dalam Media Sekolah - Dania Dwia Sulystianeu; Erlin Rintan; Muhammad Fadhil Al Mubarok; Silvi Vina Apriani; Bunyamin Maftuh; Maulia Depriya Kembara (Lembaga Pengembangan Kinerja Dosen, 2024)
One form of understanding the values contained in Pancasila and also implementation by socialization. By giving direction and understanding as well as implementation to students about Pancasila. The activity of writing this journal aims to provide a further understanding of what Pancasila is, what is its function and position and what values are contained in their precepts and how they apply in everyday life. The author conducts a series of socialization to middle, high school students, and students by asking them to what extent they know about Pancasila. Based on the socialization activities it was found that some students understood the importance of Pancasila. Meanwhile, related to the use of media, some students expressed their understanding in understanding Pancasila. This shows that the use of media through socialization activities can increase the understanding of Pancasila. Therefore, it is important for education to be able to develop learning media, especially for Pancasila education.